2016
DOI: 10.1186/s12931-016-0382-z
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to common respiratory bacteria alters the airway epithelial response to subsequent viral infection

Abstract: BackgroundColonization of the airways with potential pathogenic bacteria is observed in a number of chronic respiratory diseases, such as COPD or cystic fibrosis. Infections with respiratory viruses are known triggers of exacerbations of these diseases. We here investigated if pre-exposure to bacteria alters the response of lung epithelial cells to subsequent viral infection.MethodsBronchial epithelial cells (BEAS-2B cells and primary bronchial epithelial cells) were exposed to heat-inactivated Haemophilus inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 61 publications
(58 reference statements)
1
46
0
Order By: Relevance
“…This may have significant pathogenic consequences because exposure to common respiratory bacteria alters the airway epithelial response to subsequent viral infection. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This may have significant pathogenic consequences because exposure to common respiratory bacteria alters the airway epithelial response to subsequent viral infection. 34 …”
Section: Discussionmentioning
confidence: 99%
“…By doing so, the bacteria increase viral binding and replication of this type of virus in vitro (Gulraiz et al, 2015;Sajjan et al, 2006). Moreover, we have recently shown that H. influenzae and RSV can synergize in inducing the release of pro-inflammatory cytokines by respiratory epithelial cells (Bellinghausen et al, 2016). On the other hand, TLR3 expression, and consequently recognition of viral structures and antiviral type I/III IFN production, was shown to be impaired in bronchial epithelial cells exposed to Moraxella catarrhalis, another PPM commonly found in the LRT of COPD patients (Heinrich et al, 2016).…”
Section: Bacterial Pathogens Influencing the Response To Viral Infectionmentioning
confidence: 99%
“…In vitro studies have demonstrated the ability of H. influenzae to alter the respiratory epithelium and cause an exaggerated inflammatory response to a subsequent viral pathogen 23. There have also been data to suggest a synergistic effect between adenovirus and H. influenzae in respiratory infections 24 25.…”
Section: Discussionmentioning
confidence: 99%